2020
DOI: 10.1093/forestry/cpaa012
|View full text |Cite
|
Sign up to set email alerts
|

Auxiliary information resolution effects on small area estimation in plantation forest inventory

Abstract: In forest inventory, traditional ground-based resource assessments are often expensive and time-consuming forcing managers to reduce sample sizes to meet budgetary and logistical constraints. Small area estimation (SAE) is a class of statistical estimators that uses a combination of traditional survey data and linearly related auxiliary information to improve estimate precision. These techniques have been shown to improve the precision of stand-level inventory estimates in loblolly pine plantations using lidar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…The domain-direct estimate and its sample variance serve as the source of direct information, while the indirect information -sample estimates and variances from other domains -is then linked to the direct domain via the model y ∼ x, which leverages the relationship between sample and auxiliary data sets. Area-based approaches are often synonymous with the Fay and Herriot (1979) estimator, a well-recognized and widely adopted model used in area-based SAE, including a number of forest inventory applications (Green et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…The domain-direct estimate and its sample variance serve as the source of direct information, while the indirect information -sample estimates and variances from other domains -is then linked to the direct domain via the model y ∼ x, which leverages the relationship between sample and auxiliary data sets. Area-based approaches are often synonymous with the Fay and Herriot (1979) estimator, a well-recognized and widely adopted model used in area-based SAE, including a number of forest inventory applications (Green et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Many users of FIA data have expressed expanding needs for more detailed information on smaller spatial domains 1 www.forestfoundation.org/family-forest-carbon-program while maintaining the core field measurement program (Guldin, 2020a,b). The FIA program has responded with increased research activity in SAE (for example, Brooks et al, 2016;Nagle et al, 2019;Green et al, 2020;Coulston et al, 2021). These efforts have shown that precision can be improved using SAE with plot data combined with ancillary data.…”
Section: Introductionmentioning
confidence: 99%
“…The domain-direct estimate and its sample variance serve as the source of direct information, while the indirect information -sample estimates and variances from other domains -is then linked to the direct domain via the model y ∼ x, which leverages the relationship between sample and auxiliary data sets. Area-based approaches are often synonymous with the Fay and Herriot (1979) estimator, a well-recognized and widely adopted model used in area-based SAE, including a number of forest inventory applications (Green et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%